Skrining Fitokimia Seduhan Teh Celup Daun Insulin (Tithonia Diversifolia (Hemsl.) A. Gray) dan Daun Teh Hijau (Camellia sinensis L.) - Insani, Nurul; Kurnia, Nia Marlina; Buanawati, Vina (Jurnal Ilmiah Kesehatan Delima, 2022)
Flavonoids and saponins that have a lot of potential in the field of pharmacology. Flavonoids and saponins have a lot of potential in the field of pharmacology. The mechanism of action of saponins is by inhibiting GLUT-1 thereby reducing glucose absorption. Flavonoids in diabetes mellitus can avoid sugar absorption, stimulate glucose uptake in peripheral tissues, can also act like insulin by affecting the insulin signaling mechanism. Tannins can trigger glucose and fat metabolism so that the accumulation of these two sources of calories can be avoided, has hypoglycemic activity by increasing glycogenesis. The method is pure experimental method by conducting phytochemical screening of steeping teabags containing insulin leaves and green tea leaves. The results of phytochemical screening of insulin leaf teabags (Tithonia diversifolia (Hemsl.) A. Gray) and green tea leaves (Camellia sinensis L.) showed the presence of secondary metabolites of flavonoids, tannins and saponins.   Flavonoid dan saponin yang banyak berpotensi dalam bidang farmakologi. Mekanisme kerja saponin yaitu dengan menghambat GLUT-1 sehingga menurunkan absorbsi glukosa. Flavonoid pada Diabetes melitus dapat menghindari absorbsi gula, menstimulasi pengambilan glukosa pada jaringan perifer, juga dapat bertindak seperti insulin dengan cara mempengaruhi mekanisme insulin signaling. Tanin dapat memicu metabolisme glukosa dan lemak sehingga timbunan dari kedua sumber kalori ini dapat dihindari, memiliki aktivitas hipoglikemik dengan meningkatkan glikogenesis. Metode penelitian yang digunakan adalah eksperimental murni dengan melakukan skrining fitokimia terhadap seduhan teh celup yang mengandung daun insulin dan daun teh hijau. Hasil skrining fitokimia teh celup daun insulin (Tithonia diversifolia (Hemsl.) A. Gray) dan daun teh hijau (Camellia sinensis L.)  menunjukan adanya senyawa metabolit sekunder flavonoid, tanin dan saponin.